2018
DOI: 10.5603/fm.a2017.0085
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and morphometric analysis of idiopathic osteosclerosis in a Chilean population

Abstract: All the data observed corroborate with previous studies; the IO does not present a large difference in the Chilean population evaluated compared to pre-vious studies carried out in other populations. (Folia Morphol 2018; 77, 2: 272-278).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
16
1
10

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(36 citation statements)
references
References 14 publications
6
16
1
10
Order By: Relevance
“…Within the teeth bearing area, molar region was the commonest site (52.7%) followed by premolars region (29.9%). This was the same finding of some studies (5,24) , and on contrary to other (8,20,23) , but generally speaking, posterior region was affected much more than anterior region.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Within the teeth bearing area, molar region was the commonest site (52.7%) followed by premolars region (29.9%). This was the same finding of some studies (5,24) , and on contrary to other (8,20,23) , but generally speaking, posterior region was affected much more than anterior region.…”
Section: Discussionsupporting
confidence: 88%
“…Despite the number of cases found in females was larger than that in males, which means apparently that idiopathic osteosclerosis occurs more in females, but the reality is unlike that. As when considered the number of both genders in the sample, it showed that the percentage of occurrence in females (16.6%) is equal to it in males (16.9%), which is aligned with the results of other studies (4,21,23) , but contradicted other studies which revealed more predilection in females (8,24) and another study that revealed predilection to the other gender (22) .…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Idiopathic sclerosis was also more prevalent in the case group. This lesion must be distinguished from remnants of a past infectious lesion [ 20 ]. Thus, the need for a more thorough oral examination in order to eliminate any source of dental infection or a workup to detect secondary hyperparathyroidism is also supported in the cases of this study.…”
Section: Discussionmentioning
confidence: 99%
“…Idiopathic osteosclerosis (IO) due to increased bone production in the jaw was found as a round, elliptical, or irregular radiopaque area [ 20 ].…”
Section: Methodsmentioning
confidence: 99%